Composite film and preparation method thereof, photoelectric device and display device
By using stacked conductive materials and high-entropy alloy composite films in OLED and QLED, the problem of poor stability of the electrode film is solved, the stability and performance of the optoelectronic devices are improved, and the service life is extended.
Patent Information
- Application Number
- CN202311842301.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional OLED and QLED electrode films have poor stability and are susceptible to oxygen radicals, electric fields, thermal and mechanical effects, resulting in a decline in photoelectric performance.
A composite film arranged in a laminated manner is adopted. The first film is made of a conductive material and the second film is made of a high-entropy alloy. The composite film is formed by deposition technology to improve the stability of the electrode and the carrier injection performance.
It significantly improves the stability and service life of optoelectronic devices, prevents the diffusion of electrode layer elements, prevents external water and oxygen influence, improves charge injection and exciton generation, and improves photoelectric performance.
Smart Images

Figure CN119212434A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display technology, and in particular to a composite film and a preparation method thereof, an optoelectronic device, and a display device. Background Art
[0002] Currently, the widely used optoelectronic devices are organic light-emitting diodes (OLEDs) and quantum dot light-emitting diodes (QLEDs). OLEDs have become the mainstream technology in the field of display technology due to their excellent display performance, such as self-luminescence, simple structure, ultra-thinness, fast response speed, wide viewing angle, low power consumption, and flexible display. QLEDs have the advantages of saturated color and adjustable wavelength of emitted light, and high quantum yield of photoluminescence and electroluminescence, and have become a strong competitor to OLEDs in recent years.
[0003] The structure of traditional OLED and QLED devices generally includes an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer and a cathode. Under the action of the electric field, the holes generated by the anode of the light-emitting diode and the electrons generated by the cathode move and are injected into the hole transport layer and the electron transport layer respectively, and finally migrate to the light-emitting layer. When the two meet in the light-emitting layer, energy excitons are generated, thereby exciting the light-emitting molecules and finally producing visible light.
[0004] At present, the stability of electrode films is poor and needs further improvement. Summary of the invention
[0005] In view of this, the present application provides a composite film and a preparation method thereof, an optoelectronic device, and a display device.
[0006] The embodiment of the present application is implemented as follows: a composite film includes a first film and a second film stacked together, wherein the material of the first film includes a conductive material, and the material of the second film includes a high entropy alloy.
[0007] Accordingly, the present invention also provides a method for preparing a composite film, comprising:
[0008] Providing a conductive material, and depositing the conductive material to form a first film;
[0009] Providing a high entropy alloy, depositing the high entropy alloy to form a second film, and obtaining a composite film;
[0010] or,
[0011] Providing a high entropy alloy, and depositing the high entropy alloy to form a second film;
[0012] A conductive material is provided, and the conductive material is deposited to form a first film to obtain a composite film.
[0013] Accordingly, an embodiment of the present application further provides a photoelectric device, comprising a first electrode, an active layer, and a second electrode stacked in sequence, wherein the first electrode and / or the second electrode comprises a composite thin film;
[0014] Wherein, the composite film comprises a first film close to the active layer and a second film far away from the active layer;
[0015] The material of the first film includes a conductive material, and the material of the second film includes a high entropy alloy.
[0016] Correspondingly, an embodiment of the present application further provides a display device, which includes the above-mentioned optoelectronic device.
[0017] The composite film provided by the present application has high stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0019] Figure 1 is a schematic diagram of the structure of the composite film provided in the embodiment of the present application;
[0020] Figure 2 is a flow chart of a method for preparing a composite film provided in an embodiment of the present application;
[0021] Figure 3 is a flow chart of another method for preparing a composite film provided in an embodiment of the present application;
[0022] Figure 4 is a schematic diagram of the structure of the optoelectronic device provided in an embodiment of the present application;
[0023] Figure 5 It is a schematic diagram of the structure of another optoelectronic device provided in an embodiment of the present application.
[0024] Reference numerals:
[0025] Composite film 10; first film 11; second film 12;
[0026] A first electrode 20 ; an active layer 30 ; a second electrode 40 ; a third thin film 41 , a fourth thin film 42 ; a first carrier functional layer 50 ; and a second carrier functional layer 60 . DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0028] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0029] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0030] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or several", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0031] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0032] The thermal stability of optoelectronic devices is one of the main factors affecting their luminescence performance. The operating life of optoelectronic devices is related to the stability of their various layers. The diffusion or phase change of electrode layer elements under water, oxygen, electricity, magnetism, heat, mechanical stress and other environments will lead to the aging of the overall device life, and then cause the decline of optoelectronic performance. The influence of electrodes on the stability of optoelectronic devices is mainly reflected in the following aspects: 1. In optoelectronic devices, electrodes will diffuse to the optoelectronic functional layer under the influence of oxygen free radicals, electric fields, heat and mechanical effects, causing exciton or charge quenching; 2. Active electrodes are easily oxidized in oxygen, resulting in an increase in square resistance and a decline in the electrical performance of the device.
[0033] The technical solution of this application is as follows:
[0034] First, see Figure 1 An embodiment of the present application provides a composite film 10, comprising a first film 11 and a second film 12 which are stacked, wherein the material of the first film 11 comprises a conductive material, and the material of the second film 12 comprises a high entropy alloy.
[0035] It should be noted that high-entropy alloys (HEA) are alloys formed by five or more equal or approximately equal amounts of metals. The specific strength of high-entropy alloys is higher than that of traditional alloys, and their fracture resistance, tensile strength, corrosion resistance and oxidation resistance are better than those of traditional alloys. This is because when the degree of disorder increases, the system becomes more stable. When enough elements are mixed together in equal proportions, the resulting mixed system has a high degree of disorder, which can prevent the formation of clusters that cause the system to become embrittled. According to the high entropy effect in thermodynamics, the mixing Gibbs free energy of the mixed system decreases as the mixing entropy increases, thereby promoting the system to form a quasi-single-phase structure with a highly stable state.
[0036] The composite film 10 provided in the present application includes a first film 11 formed of a conductive material and a second film 12 formed of a high entropy alloy. The conductive material ensures a suitable carrier injection energy level for the composite film 10, and the high entropy alloy ensures the overall stability of the composite film 10 and prevents the influence of external water, oxygen and other environments.
[0037] In some embodiments, the conductive material includes an electrode material, and the electrode material includes one or more of a metal material, a carbon material, and a metal oxide.
[0038] Furthermore, the metal material includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, Pt and Mg.
[0039] The carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber.
[0040] The metal oxide includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, MoO3 and AMO.
[0041] In some embodiments, the high entropy alloy includes 5 or more metals.
[0042] Furthermore, the work function of the metal is equal to or greater than 3.8 eV, for example, equal to or greater than 3.9 V, equal to or greater than 4 V, equal to or greater than 4.2 V, equal to or greater than 4.5 V, etc. In this way, the carriers injected into the composite film 10 can be balanced, and the stability of the composite film 10 can be ensured, and it is not easy to be oxidized and deteriorated.
[0043] The electrical conductivity of the metal is equal to or greater than 0.8×10 7 S / m, for example, can be equal to or greater than 1×10 7 S / m, equal to or greater than 1.2×10 7 S / m, equal to or greater than 1.5×10 7 S / m, equal to or greater than 1.8×10 7 S / m, equal to or greater than 2×10 7 S / m, equal to or greater than 2.2×10 7 S / m, equal to or greater than 2.5×10 7 S / m, etc. This is beneficial to reducing the resistance of the composite film 10 and improving the stability of the composite film 10.
[0044] In some embodiments, the molar percentage of each metal in the high entropy alloy is 5% to 35%, for example, 10%, 15%, 20%, 25%, 30%, etc. Within the molar percentage range, the disorder of the high entropy alloy is appropriate, so that the second film 12 is more stable. It should be noted that the molar percentage of each metal in the high entropy alloy is 100%.
[0045] In some embodiments, the metal includes one or more of Pt, Ir, Ni, Au, Co, Be, Rh, Os, Ru, Cu, Mo, W, Fe, Zn, Nb, Al, Ag, Ta, Cd, In or Ti.
[0046] In some embodiments, the metal is selected from a first metal.
[0047] Furthermore, the work function of the first metal is 4 eV to 5.2 eV, for example, 4.2 eV, 4.4 eV, 4.6 eV, 4.8 eV, 5 eV, etc.; the conductivity is equal to or greater than 2.5×10 7 S / m, for example, can be 2.6×10 7 S / m, 2.8×107 S / m, 3×10 7 S / m, etc. Within the above range, it is beneficial to ensure the conductivity of the composite film 10.
[0048] In some embodiments, the first metal includes one or more of Au, Ag, Al, Cu, and Be.
[0049] It should be noted that the high entropy alloy may contain only the first metal, such as AuAgAlCuBe alloy.
[0050] In some embodiments, the metal is selected from a first metal and a second metal. In other words, the high entropy alloy contains both the first metal and the second metal.
[0051] In some embodiments, the second metal includes one or more of Pt, Ir, Ni, Co, Rh, Os, Ru, Mo, W, Fe, Zn, Nb, Ta, Cd, In or Ti.
[0052] In some embodiments, when the metal is selected from the first metal and the second metal, the molar fraction of the second metal in the high entropy alloy is 5% to 95%, for example, 10%, 20%, 50%, 60%, 80%, etc. Within the molar ratio range, the first metal and the second metal can fully improve the conductivity of the composite film 10.
[0053] In some embodiments, the high entropy alloy includes one or more of AgAlAuCuTi alloy, AgAlAuCuIr alloy, AgAlAuCuNi alloy, AgAlAuCuCo alloy, AgAlAuCuMo alloy, AgAlAuCuW alloy, AgAlAuCuFe alloy, AgAlAuCuZn alloy, AgAlAuCuTa alloy, AuAgAlCuBe alloy, AgAlAuCuCd alloy, AgAlAuCuIn alloy, AgAlAuIrNi alloy, AgAlAuNiAu, AgAlAuIrNiRhOs alloy, AgAlAuNiPtIr alloy, ZnMoAuFeInCdWCo alloy, and RhRuNbAgFeCuAlCdInNiIrZnBeOsT alloy.
[0054] It should be noted that the preparation method of the high entropy alloy can adopt the common alloy preparation method in the art, such as smelting method, powder metallurgy method, chemical synthesis method, solution infiltration method, electrochemical method, electron beam evaporation method, etc. It is understood that the high entropy alloy can also be purchased.
[0055] Exemplarily, the melting method includes vacuum arc melting, and the preparation method of the AgAlAuCuTi alloy includes:
[0056] High-purity metals Ag, Al, Au, Cu, and Ti are mixed according to the required molar ratio of each element, and the sample is melted in an electric arc furnace under the protection of high-purity argon. The melting is repeated to ensure uniform ingot casting, thereby forming an AgAlAuCuTi alloy.
[0057] In some embodiments, the thickness ratio of the first film 11 to the second film 12 is (1-30): (1-30), for example, 15:5, 15:10, 15:15, 15:20, 15:25, 5:15, 10:15, 20:15, 25:20. Within the range of the thickness ratio, it is beneficial to ensure the carrier injection performance and stability of the composite film 10.
[0058] In some embodiments, the composite film 10 has a thickness of 1 nm to 10000 nm, for example, 10 nm, 20 nm, 50 nm, 100 nm, 200 nm, 500 nm, 1000 nm, 2000 nm, 5000 nm, etc.
[0059] Second, see Figure 2 The present application also provides a method for preparing a composite film 10, comprising:
[0060] S11, providing a conductive material, and depositing the conductive material to form a first film 11;
[0061] S12, providing a high entropy alloy, depositing the high entropy alloy to form a second film 12, and obtaining a composite film 10.
[0062] It should be noted that the order of forming the first film 11 and the second film 12 is not limited. For example, in other embodiments, the second film 12 may be formed first, and then the first film 11 may be formed.
[0063] Specifically, see Figure 3 , the preparation method of the composite film 10 comprises:
[0064] S21, providing a high entropy alloy, and depositing the high entropy alloy to form a second film 12;
[0065] S22 , providing a conductive material, depositing the conductive material to form a first film 11 , and obtaining a composite film 10 .
[0066] It can be understood that the formation of the first film 11 and the second film 12 can be achieved by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. The physical method includes physical coating and solution method, among which the physical coating method includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion coating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; the solution method can be spin coating, printing, inkjet printing, scraping, printing, dip pulling, immersion, spraying, roll coating, casting, slit coating, and strip coating. Among them, the spraying method includes thermal spraying, plasma spraying, or cold spraying.
[0067] Preferably, the first thin film 11 and the second thin film 12 are formed by a coating method.
[0068] Specifically, in some embodiments, the method for forming the first film 11 includes: depositing the conductive material by first evaporation to form the first film 11 .
[0069] Furthermore, the vacuum degree of the first evaporation is 8×10 -6 Pa~8×10 -3 Pa, for example, can be 8×10 - 5 Pa, 8×10 -4 Pa, etc.; the rate is For example, it can be etc.; the power is 500W~2000W, for example, it can be 800W, 1000W, 1200W, 1500W, 1800W, etc.; the temperature is 50℃~200℃, for example, it can be 80℃, 100℃, 120℃, 150℃, 180℃, etc.
[0070] In some other embodiments, the method for forming the second film 12 includes: depositing the high entropy alloy by a second evaporation to form the second film 12.
[0071] Furthermore, the vacuum degree of the second evaporation is 8×10 -6 Pa~8×10 -3 Pa, for example, can be 8×10 - 5 Pa, 8×10 -4 Pa, etc.; the rate is For example, it can be etc.; the power is 500W~2000W, for example, it can be 800W, 1000W, 1200W, 1500W, 1800W, etc.; the temperature is 50℃~200℃, for example, it can be 80℃, 100℃, 120℃, 150℃, 180℃, etc.
[0072] It can be understood that in some embodiments, the depositing of high entropy alloy includes depositing high entropy alloy on the substrate to form a first film 11; and the depositing of conductive material includes depositing conductive material on the first film 11 to form a second film 12.
[0073] In other embodiments, the depositing of the conductive material includes depositing the conductive material on the substrate to form the second film 12 ; and the depositing of the high entropy alloy includes depositing the high entropy alloy on the second film 12 to form the first film 11 .
[0074] In some embodiments, the substrate may be a rigid substrate or a flexible substrate. Further, the material of the substrate may be selected from but not limited to at least one of glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide and polyether sulfone.
[0075] It should be noted that the composite film 10 is a composite electrode, which can be applied to any field requiring an electrode, such as a light emitting diode, a field effect transistor, and the like.
[0076] Third, see Figure 4 and Figure 5 , the embodiment of the present application further provides a photoelectric device, comprising a first electrode 20, an active layer 30, and a second electrode 40 stacked in sequence, wherein the first electrode 20 and / or the second electrode 40 comprises a composite film 10;
[0077] The composite film 10 includes a first film 11 close to the active layer 30 and a second film 12 far from the active layer 30;
[0078] The material of the first film 11 includes a conductive material, and the material of the second film 12 includes a high entropy alloy.
[0079] In the optoelectronic device provided by the present application, the first film 11 close to the active layer 30 ensures the appropriate carrier injection energy level, while the second film 12 far from the active layer 30 ensures the overall stability of the device, thereby improving the stability and service life of the optoelectronic device. The first composite film 10 prevents the elements of the electrode layer from diffusing to the active layer 30, which quenches the charge or exciton; the high stability of the second film 12 itself also prevents the optoelectronic device from being affected by the external environment such as water and oxygen; the first film 11 can effectively avoid the problems such as difficulty in charge injection caused by the energy level mismatch between the second film 12 and the active layer 30, significantly improving the performance and service life of the optoelectronic device, and improving the flexibility of the selection of high entropy alloy components.
[0080] In some embodiments, the material of the active layer 30 includes a light-emitting material.
[0081] In some embodiments, the material of the active layer 30 includes one or more of an organic light-emitting material and a quantum dot light-emitting material.
[0082] The organic light-emitting material can be selected from but not limited to CBP:Ir(mppy)3(4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine iridium(III)]), TCTX:Ir(mmpy)(4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine iridium]), diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF (thermally activated delay) materials, polymers containing covalent bonds of BN, HLCT (hybridized localized charge transfer excited state) materials, and Exciplex (exciplex) light-emitting materials.
[0083] The quantum dot light-emitting material may be selected from, but not limited to, one or more of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials.
[0084] The material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot can be selected from but not limited to one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The shell of the core-shell structure quantum dot is one or more layers. The II-VI group compound can be selected from but not limited to one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe. The IV-VI group compound can be selected from but not limited to one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The III-V group compound may be selected from, but not limited to, one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, and InAlPSb. The I-III-VI group compound may be selected from, but not limited to, one or more of CuInS2, CuInSe2, and AgInS2.
[0085] As an example, the core-shell structure quantum dots can be selected from but not limited to one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS. The “ / ” in the above expressions such as CdSe / ZnS means that the substance after the “ / ” (as a shell layer) covers the substance before the “ / ” (as a core layer).
[0086] The general structural formula of the perovskite quantum dot is AMX3, wherein A is selected from Cs + 、CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is selected from Cl - Br - ,I - One or more of the .
[0087] In some embodiments, the optoelectronic device further includes one or more of a first carrier functional layer 50 and a second carrier functional layer 60. The first carrier functional layer 50 is located between the first electrode 20 and the active layer 30, and the second carrier functional layer 60 is located between the second electrode 40 and the active layer 30.
[0088] In some embodiments, the first electrode 20 is an anode, the first carrier functional layer 50 is a hole functional layer, the second carrier functional layer 60 is an electron functional layer, and the second electrode 40 is a cathode.
[0089] In some other embodiments, the first electrode 20 is a cathode, the first carrier functional layer 50 is an electron functional layer, the second carrier functional layer 60 is a hole functional layer, and the second electrode 40 is an anode.
[0090] The electronic functional layer includes one or more of an electron injection layer and an electron transport layer.
[0091] The hole functional layer includes one or more of a hole injection layer and a hole transport layer.
[0092] In some embodiments, the material of the electronic functional layer includes one or more of a first doped metal oxide particle, a first undoped metal oxide particle, a IIB-VIA semiconductor material, a IIIA-VA semiconductor material, and an IB-IIIA-VIA semiconductor material. The material of the first undoped metal oxide particle includes one or more of ZnO, TiO2, SnO2, ZrO2, and Ta2O5. The metal oxide in the first doped metal oxide particle includes one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and Al2O3. The doping element in the first doped metal oxide particle includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga. The IIB-VIA semiconductor material includes one or more of ZnS, ZnSe, and CdS. The IIIA-VA semiconductor material includes one or more of InP and GaP. The IB-IIIA-VIA semiconductor material includes one or more of CuInS and CuGaS.
[0093] In some embodiments, the material of the hole functional layer includes 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazol-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green emission Optical materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylene vinylene), poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)- 1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraaryl benzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinyl carbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenyl benzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, second doped metal oxide The invention relates to a method for preparing an aqueous solution of at least one doped metal oxide particle, a second non-doped metal oxide particle, a metal sulfide, a metal selenide and a metal nitride, wherein the metal oxide in the second doped metal oxide particle and the metal oxide in the second non-doped metal oxide particle independently include one or more of MoO3, WO3, NiO, CrO3, CuO and V2O5, the doping element in the second doped metal oxide particle includes one or more of Mo, W, Ni, Cr, Cu and V, the metal sulfide includes one or more of CuS, MoS3 and WS3, the metal selenide includes one or more of MoSe3 and WSe3, and the metal nitride includes P-type gallium nitride.
[0094] In a fourth aspect, an embodiment of the present application further provides a display device, which includes the above-mentioned optoelectronic device.
[0095] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.
[0096] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0097] Example 1
[0098] This embodiment provides a composite film, including a first film and a second film, wherein the material of the first film includes Ag, and the material of the second film includes AgAlAuCuTi alloy, and the preparation method thereof is as follows:
[0099] Providing a substrate, placing it in a vapor deposition chamber, and thermally evaporating a single silver substance through a mask plate to form a first thin film with a thickness of 20 nm;
[0100] An electron beam evaporation method is adopted to provide AgAlAuCuTi alloy, and the AgAlAuCuTi alloy is evaporated on the first film, and the molar percentage of each metal is 20%, so as to form a second film with a thickness of 20nm; and a film is obtained.
[0101] Example 2
[0102] Example 2 is substantially the same as Example 1, except that in the AgAlAuCuTi alloy in Example 2, the molar percentages of the metals are 5%, 10%, 15%, 20% and 25% respectively.
[0103] Example 3
[0104] Example 3 is substantially the same as Example 1, except that in the AgAlAuCuTi alloy in Example 3, the molar percentages of the metals are 35%, 30%, 20%, 10% and 5% respectively.
[0105] Example 4
[0106] Example 4 is basically the same as Example 1, with the only difference being that the high entropy alloy in Example 4 is a ZnMoAuFeInCdWCo alloy, and the molar percentages of each metal are 10%, 15%, 10%, 15%, 15%, 10%, 15% and 10%, respectively.
[0107] Example 5
[0108] Example 5 is basically the same as Example 1, the only difference is that the high entropy alloy in Example 5 is RhRuNbAgFeCuAlCdInNiIrZnBeOsTa alloy, and the molar percentages of each metal are 5%, 5%, 5%, 5%, 5%, 5%, 5%, 5%, 5%, 5%, 5%, 10%, 10%, 10%, 10% and 10% respectively.
[0109] Example 6
[0110] Example 6 is basically the same as Example 1, except that in Example 6, the silver of the first film is replaced by ITO.
[0111] Example 7
[0112] Example 7 is substantially the same as Example 1, except that the silver of the first film in Example 6 is replaced by graphene.
[0113] Example 8
[0114] Example 8 is substantially the same as Example 1, except that in Example 8, the thickness of the first film is 10 nm, and the thickness of the second film is 30 nm.
[0115] Example 9
[0116] Example 9 is substantially the same as Example 1, except that the thickness of the first film in Example 9 is 30 nm, while the thickness of the first film in Example 1 is 40 nm.
[0117] Comparative Example 1
[0118] This comparative example provides a film, namely the first film in Example 1.
[0119] Comparative Example 2
[0120] This comparative example provides a film, namely the second film in Example 1.
[0121] The corrosion resistance (chemical stability), bending resistance (physical stability), self-corrosion potential (Ecorr) and conductivity stability of the composite films and films of Examples 1 to 9 and Comparative Examples 1 to 3 were tested. The test results are shown in Table 1.
[0122] Among them, the test method for corrosion resistance is: self-corrosion potential in a H2SO4 solution with a concentration of 1 mol / L. Self-corrosion potential (Ecorr) is a specific corrosion system, and the metal potential is measured without an applied current. The larger the negative value of Ecorr, the greater the corrosion tendency; the larger the positive value, the smaller the corrosion tendency.
[0123] The test method for bending resistance is: measuring the conductivity change after being bent 500 times with a bending radius of 3 mm (σ2 / σ1, σ2 is the conductivity after bending; σ1 is the conductivity after bending).
[0124] Table 1
[0125]
[0126]
[0127] From Table 1, we can see that:
[0128] It can be seen from Examples 1 to 3 and Comparative Example 1 that the negative value of the self-corrosion potential of the composite film provided by the present application is significantly lower than that of Comparative Example 1, indicating that the composite film is more resistant to chemical corrosion, and after bending treatment, the conductivity changes less, indicating that the composite film has strong resistance to mechanical fatigue and higher stability;
[0129] It can be seen from Examples 1, 4 to 5 and Comparative Example 1 that replacing the proportion of each metal in the high entropy alloy has little effect on the self-corrosion potential of the composite film, and the conductivity remains at 97% after bending, and the chemical stability and physical stability are both high;
[0130] It can be seen from Examples 1, 6 to 7 and Comparative Example 1 that when the first film is a metal oxide, the corrosion resistance is not as good as that of metal and carbon materials, and the bending resistance is also slightly worse than that of metal and carbon materials, but compared with Comparative Example 1, it still has higher corrosion resistance and mechanical stability;
[0131] It can be seen from Examples 1, 8 to 9 and Comparative Example 1 that the greater the thickness of the second film, i.e., the high entropy alloy film, the better the improvement effect on the composite film. The composite film of Example 8 has a smaller corrosion tendency, and after multiple bending, the conductivity decreases less;
[0132] It can be seen from Example 1 and Comparative Example 2 that the film containing only one layer of high entropy alloy has a lower negative self-corrosion potential, is more corrosion-resistant, has good chemical stability, and its conductivity remains at 99% after bending, has good bending resistance, and good physical stability.
[0133] Device Example 1
[0134] This embodiment provides a photoelectric device, and the preparation method is as follows:
[0135] The substrate with the patterned electrode is cleaned; the surface of the ITO substrate is treated with ultraviolet-ozone for 5 minutes to further remove organic matter attached to the surface of the ITO substrate and improve the work function of the ITO substrate.
[0136] A hole injection layer PEDOT:PSS with a thickness of 30 nm was deposited on the ITO substrate treated in the previous step, and the substrate was placed on a heating table at 150°C and heated for 30 minutes;
[0137] A hole transport layer TFB with a thickness of 40 nm was deposited on the hole injection layer, and the substrate was placed on a heating table at 150° C. and heated for 20 min;
[0138] The CdSe / ZnS core-shell structure quantum dot solution was spin-coated on the hole transport layer, and then placed on a hot plate at 100°C for annealing for 15 minutes to complete the preparation of a quantum dot light-emitting layer with a thickness of about 30 nm;
[0139] A ZnO electron transport layer is deposited on the quantum dot layer. After the deposition is completed, the wafer is placed on a heating table at 80°C and heated for 30 minutes. The thickness of the layer is 30 nm.
[0140] A composite thin film is prepared on the electron transport layer according to the composite thin film preparation method of Example 1 to form a cathode.
[0141] Encapsulation is performed to obtain an optoelectronic device.
[0142] Device Examples 2 to 9
[0143] Device Examples 2 to 9 are substantially the same as Device Example 1, with the only difference being that the cathodes in Device Examples 2 to 9 are prepared by the methods of Examples 2 to 9, respectively.
[0144] Device Example 10
[0145] Device Example 10 is basically the same as Device Example 1, with the only difference being that in Device Example 10, a composite thin film is prepared according to the preparation method of the second thin film and the first thin film to form an anode, and then a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer and a cathode are sequentially prepared on the first thin film, and a layer of Ag is directly evaporated on the cathode.
[0146] Device Example 11
[0147] Device Example 11 is basically the same as Device Example 1, with the only difference being that the anode in Device Example 11 is prepared with reference to Device Example 10, while the cathode is prepared with reference to Device Example 1.
[0148] Device Comparison Example 1
[0149] Device Comparative Example 1 is substantially the same as Device Example 1, except that the cathode in Device Comparative Example 1 is prepared by the method of Reference Example 1.
[0150] Device Comparison Example 2
[0151] Device Comparative Example 2 is substantially the same as Device Example 1, except that the cathode in Device Comparative Example 2 is prepared by the method of Reference Example 2.
[0152] Device Comparison Example 3
[0153] Device Comparative Example 3 is substantially the same as Device Example 10, except that the anode in Device Comparative Example 3 does not contain the first film but only contains the second film.
[0154] The external quantum efficiency EQE and the lifetime T95@1000nit of the optoelectronic devices of device embodiments 1 to 11 and device comparative examples 1 to 3 were tested respectively, and the results are shown in Table 2.
[0155] Among them, the test method of external quantum efficiency EQE is: the ratio of the number of electron-hole pairs injected into quantum dots to the number of emitted photons, the unit is %, which is an important parameter to measure the quality of electroluminescent devices, and can be obtained by measuring with EQE optical testing instruments. The specific calculation formula is as follows:
[0156]
[0157] Among them, η e is the light output coupling efficiency, η r is the ratio of the number of recombined carriers to the number of injected carriers, χ is the ratio of the number of photon-generating excitons to the total number of excitons, K R is the radiation process rate, K NR is the rate of the non-radiative process.
[0158] Test conditions: carried out at room temperature, air humidity is 30-60%.
[0159] The test method for the life span T95@1000nit is: the time required for the device to reduce its brightness to a certain proportion of the maximum brightness under constant current or voltage driving. The time when the brightness drops to 95% of the maximum brightness is defined as T95, and this life span is the measured life span. In order to shorten the test cycle, the device life span test is usually carried out at high brightness by accelerating device aging, and the life span at high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula. For example, the life span at 1000nit is calculated as T95@1000nit. The specific calculation formula is as follows:
[0160]
[0161] Among them, T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, and this experiment measured the lifespan of several groups of QLED devices at rated brightness and found that the A value was 1.7.
[0162] Table 2
[0163]
[0164] From Table 2, we can see that:
[0165] It can be seen from device embodiments 1 to 3 and device comparative example 1 that the external quantum efficiency and service life of the composite film provided in the present application are significantly improved compared with device comparative example 1, indicating that the composite film is applied as an electrode to a photoelectric device, which can significantly improve the performance of the photoelectric device;
[0166] It can be seen from device examples 1, 4-5 and device comparative example 1 that replacing the proportion of each metal in the high entropy alloy has no significant effect on the performance of the composite film, and thus there is no significant difference between the performance of the optoelectronic devices of device examples 1, 4-5, and both can improve the external quantum efficiency and service life of the optoelectronic devices;
[0167] It can be seen from device embodiments 1, 6 to 7 and device comparative example 1 that when the first film is a metal material, a metal oxide or carbon, the external quantum efficiency of the optoelectronic device is the highest and the service life is longer when the first film is a metal. This may be because the energy levels of the metal electrode and the functional layer are more matched, which can promote the injection of carriers, thereby improving the performance of the optoelectronic device;
[0168] It can be seen from device embodiments 1, 8 to 9 and device comparative example 1 that the thickness of the first film and the second film have little difference in effect on the performance of the optoelectronic device, and both can effectively improve the external quantum efficiency of the optoelectronic device and extend the service life of the optoelectronic device;
[0169] It can be seen from device embodiments 1, 8 to 9 and device comparative example 1 that the thickness of the first film and the second film have little effect on the performance of the optoelectronic device;
[0170] It can be seen from device embodiments 1, 10 to 11 and device comparison examples 2 to 3 that when the anode and the cathode simultaneously adopt the composite film provided by the present application, the external quantum efficiency of the photoelectric device has no significant change compared with other embodiments, but the service life is significantly improved. This may be because the composite film improves the stability of the photoelectric device, thereby extending the service life; compared with the device embodiments, the external quantum efficiency of the photoelectric devices of device comparison examples 2 to 3 is significantly reduced, even worse than that of device comparison example 1, and the service life is also significantly shortened compared with the device embodiments, which is slightly improved compared with device comparison example 1.
[0171] In summary, the composite film provided by the present application is used as an electrode in a photoelectric device, which can significantly improve the external quantum efficiency of the photoelectric device, extend the service life of the photoelectric device, and improve the stability of the photoelectric device.
[0172] The composite film and its preparation method, optoelectronic device, and display device provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A composite film, characterized in that: The invention comprises a first film and a second film which are stacked, wherein the material of the first film comprises a conductive material, and the material of the second film comprises a high entropy alloy.
2. The composite film according to claim 1, characterized in that The conductive material includes an electrode material, and the electrode material includes one or more of a metal material, a carbon material and a metal oxide; and / or The high entropy alloy includes 5 or more metals.
3. The composite film according to claim 2, characterized in that The metal material includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, Pt and Mg; and / or The carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; and / or The metal oxide includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, MoO3 and AMO; and / or The work function of the metal is equal to or greater than 3.8 eV; and / or The electrical conductivity of the metal is equal to or greater than 0.8×10 7 S / m; and / or In the high entropy alloy, the molar percentage of each metal is 5% to 35%; and / or The metal includes Pt, Ir, Ni, Au, Co, Be, Rh, Os, Ru, Cu, Mo, W, Fe, Zn, Nb, Al, Ag, Ta, Cd, In or Ti.
4. The composite film according to claim 2, characterized in that The metal is selected from a first metal, or a first metal and a second metal; The work function of the first metal is 4 eV to 5.2 eV; and / or The electrical conductivity of the first metal is equal to or greater than 2.5×10 7 S / m; and / or The first metal includes one or more of Au, Ag, Al, Cu, and Be; and / or The second metal comprises one or more of Pt, Ir, Ni, Co, Rh, Os, Ru, Mo, W, Fe, Zn, Nb, Ta, Cd, In or Ti; and / or When the metal is selected from the first metal and the second metal, the molar fraction of the second metal in the high entropy alloy is 5% to 95%.
5. The composite film according to claim 1, characterized in that The high entropy alloy includes one or more of AgAlAuCuTi alloy, AgAlAuCuIr alloy, AgAlAuCuNi alloy, AgAlAuCuCo alloy, AgAlAuCuMo alloy, AgAlAuCuW alloy, AgAlAuCuFe alloy, AgAlAuCuZn alloy, AgAlAuCuTa alloy, AuAgAlCuBe alloy, AgAlAuCuCd alloy, AgAlAuCuIn alloy, AgAlAuIrNi alloy, AgAlAuNiAu, AgAlAuIrNiRhOs alloy, AgAlAuNiPtIr alloy, ZnMoAuFeInCdWCo alloy, RhRuNbAgFeCuAlCdInNiIrZnBeOsTa alloy; and / or The thickness ratio of the first film to the second film is (1-30): (1-30); and / or The thickness of the composite film is 1 nm to 10000 nm.
6. A method for preparing a composite film, characterized in that: include: Providing a conductive material, and depositing the conductive material to form a first film; Providing a high entropy alloy, depositing the high entropy alloy to form a second film, and obtaining a composite film; or, Providing a high entropy alloy, and depositing the high entropy alloy to form a second film; A conductive material is provided, and the conductive material is deposited to form a first film to obtain a composite film.
7. The preparation method according to claim 6, characterized in that: The conductive material includes an electrode material, and the electrode material includes one or more of a metal material, a carbon material and a metal oxide; and / or The high entropy alloy includes five or more metals; the work function of the metal is equal to or greater than 3.8 eV; the electrical conductivity of the metal is equal to or greater than 0.8×10 7 S / m; in the high entropy alloy, the molar percentage of each metal is 5% to 35%; the metal includes one or more of Pt, Ir, Ni, Au, Co, Be, Rh, Os, Ru, Cu, Mo, W, Fe, Zn, Nb, Al, Ag, Ta, Cd, In or Ti.
8. The preparation method according to claim 7, characterized in that: The metal material includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, Pt and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, MoO3 and AMO; and / or The high entropy alloy includes one or more of AgAlAuCuTi alloy, AgAlAuCuIr alloy, AgAlAuCuNi alloy, AgAlAuCuCo alloy, AgAlAuCuMo alloy, AgAlAuCuW alloy, AgAlAuCuFe alloy, AgAlAuCuZn alloy, AgAlAuCuTa alloy, AuAgAlCuBe alloy, AgAlAuCuCd alloy, AgAlAuCuIn alloy, AgAlAuIrNi alloy, AgAlAuNiAu, AgAlAuIrNiRhOs alloy, AgAlAuNiPtIr alloy, ZnMoAuFeInCdWCo alloy, and RhRuNbAgFeCuAlCdInNiIrZnBeOsTa alloy.
9. The preparation method according to claim 8, characterized in that: The method for forming the first thin film comprises: depositing the conductive material by first evaporation to form the first thin film; and / or The method for forming the second thin film includes: depositing the high entropy alloy by second evaporation to form the second thin film.
10. The preparation method according to claim 9, characterized in that: The vacuum degree of the first evaporation is 8×10 -6 Pa~8×10 -3 Pa; the rate is Power is 500W~2000W; Temperature is 50℃~200℃; and / or The vacuum degree of the second evaporation is 8×10 -6 Pa~8×10 -3 Pa; the rate is The power is 500W~2000W; the temperature is 50℃~200℃.
11. A photoelectric device, characterized in that: It comprises a first electrode, an active layer and a second electrode which are stacked in sequence, wherein the first electrode and / or the second electrode comprises a composite film; Wherein, the composite film includes a first film close to the active layer and a second film far away from the active layer; The material of the first film includes a conductive material, and the material of the second film includes a high entropy alloy.
12. The optoelectronic device according to claim 11, characterized in that The optoelectronic device further includes one or more of a first carrier functional layer and a second carrier functional layer; the first carrier functional layer is located between the first electrode and the active layer, and the second carrier functional layer is located between the second electrode and the active layer; The first electrode is an anode, the first carrier functional layer is a hole functional layer, the second carrier functional layer is an electron functional layer, and the second electrode is a cathode; or, the first electrode is a cathode, the first carrier functional layer is an electron functional layer, the second carrier functional layer is a hole functional layer, and the second electrode is an anode.
13. The optoelectronic device according to claim 12, characterized in that The material of the active layer includes a luminescent material; the luminescent material includes one or more of an organic luminescent material and a quantum dot luminescent material; the organic luminescent material is selected from 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine iridium(III)], 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine iridium], diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, extended One or more of delayed fluorescent materials, TTA materials, TADF materials, polymers containing BN covalent bonding, HLCT materials, and Exciplex luminescent materials; the quantum dot luminescent material is selected from one or more of single structure quantum dots, core-shell structure quantum dots, and perovskite semiconductor materials; the material of the single structure quantum dots, the core material of the core-shell structure quantum dots, and the shell material of the core-shell structure quantum dots are selected from one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds, and I-III-VI group compounds; the core-shell structure quantum dots are selected from one or more of The shell layer of the sub-dot is one or more layers; the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZn SeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe;The III-V compound is selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAl One or more of NSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from one or more of CuInS2, CuInSe2 and AgInS2; the core-shell structure quantum dots are selected from one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS; the general structural formula of the perovskite quantum dots is AMX3, wherein A is selected from Cs; + 、CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is selected from Cl - Br - ,I - One or more of; and / or The material of the electronic functional layer includes one or more of a first doped metal oxide particle, a first undoped metal oxide particle, a IIB-VIA semiconductor material, a IIIA-VA semiconductor material and an IB-IIIA-VIA semiconductor material, the material of the first undoped metal oxide particle includes one or more of ZnO, TiO2, SnO2, ZrO2, and Ta2O5, the metal oxide in the first doped metal oxide particle includes one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and Al2O3, the doping element in the first doped metal oxide particle includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga, the IIB-VIA semiconductor material includes one or more of ZnS, ZnSe, and CdS, the IIIA-VA semiconductor material includes one or more of InP and GaP, and the IB-IIIA-VIA semiconductor material includes one or more of CuInS and CuGaS; and / or The materials of the hole functional layer include 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazol-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2, 3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylene vinylene), poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4- Phenylene vinylene], copper phthalocyanine, aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraaryl benzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinyl carbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenyl benzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, second doped metal oxide Particles, one or more of the second non-doped metal oxide particles, metal sulfides, metal selenides and metal nitrides, the metal oxide in the second doped metal oxide particles and the metal oxide in the second non-doped metal oxide particles each independently include one or more of MoO3, WO3, NiO, CrO3, CuO, V2O5, the doping elements in the second doped metal oxide particles include one or more of Mo, W, Ni, Cr, Cu, V, the metal sulfide includes one or more of CuS, MoS3, WS3, the metal selenide includes one or more of MoSe3, WSe3, and the metal nitride includes P-type gallium nitride.
14. A display device, characterized in that: The invention comprises a photoelectric device as claimed in any one of claims 11 to 13.